Modeling craniofacial spliceosomopathies: a pathway toward deciphering disease mechanisms - Griffin, Casey (Frontiers in Cell and Developmental Biology, 2025)
Craniofacial spliceosomopathies are syndromes resulting from mutations in components of the spliceosome, presenting with facial dysostosis in combination with other phenotypes. An outstanding question in the field is how mutations in the ubiquitously expressed spliceosome lead to such cell- and tissue-specific disorders. To understand the etiology of these diseases and decipher the underlying mechanisms, scientists have turned to modeling these disorders in the laboratory. In vivo modeling of these disorders includes the use of mice, zebrafish, and frogs, whereas in vitro modeling typically uses embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs). The goal with these models is to recapitulate the human disorders in a manner that is conducive to scientific exploration. In this review, we briefly describe the major craniofacial spliceosomopathies and discuss recent advances using model systems that have helped understand the root cause of these conditions.